EFFECT OF CHITOSAN CONCENTRATION ON PHYSICAL CHARACTERISTICS OF EXTRACT ETHANOLIC OF BAY LEAF (Syzygium polyanthum) NANOPARTICLE PREPARED BY CROSS-LINKING METHODS - Rahayyu, Annisa Maulidia; Hidayati, Evi Nurul; Masruriwati, Eni (Jurnal Farmasi Sains dan Praktis, 2024)
Chitosan is a natural cationic polysaccharide that could form bonds with negatively charged polyanions like sodium tripolyphosphate (STPP) as a crosslinker. One of the important factors to develop nanoparticles is the concentration of polymer. The increased polymer concentration will increase the viscosity of the solution formed, and the size of the nanoparticles created will increase. However, if the amount of polymer is too small, the particles formed are smaller, and aggregation could be formed. In this study, the ethanolic extract of bay leaf (Syzygium polyanthum) was used as a drug that has a potent anti-dyslipidemia effect by lowering cholesterol and triglyceride levels. Studies on the ethanolic extract of a bay leaf as an anti-dyslipidemia are still limited. The objective of this research was an investigate effect of the chitosan concentration used 0.6 mg/ml (F1); 1mg/ml (F2); and 1.4 mg/ml (F3) on the physical characteristics of ethanolic extract of bay leaf (Syzygium polyanthum) nanoparticles (NSPs) prepared by cross-linking methods. The result of particle size evaluation showed that the particle size was 665.1 nm ± 14.71 (F1); 180.1 nm ± 0.5; and 221.35 nm ± 1.91 (F3), while the polydispersity index F1, F2, and F3 were 0.773 ± 0.152; 0.220 ± 0.016; and 0.212 ± 0.024 respectively. The results of this study found F2 was the most optimal chitosan concentration with particle size under 200 nm, and polydispersity index under 0.5 with positive ζ-potential value. In conclusion, chitosan concentration showed has an effect on the physical characteristics of the nanoparticles.